Moon over Malaya the 2nd Argylls and Plymouth Argyll Royal Marines in Malaya and Singapore - McCormick, Audrey Holmes (History Press, 2002)
What really happened in Singapore and Malaya during the dark days of December 1941 to February 1942? Contrary to received wisdom, Singapore was not given up without a fight, as the testimony of the men interviewed here attests. For many of course, escape was not possible and they ended up in the notorious Japanese POW camps. Their suffering also forms part of this classic study. The fighting at the Slim River in Malaya in January 1942, a rearguard to keep the Japanese back until reinforcements could reach Singapore, is dramatic enough on its own. Seven Battalion commanders would die there.